PPARγ3 mRNA: a distinct PPARγ mRNA subtype transcribed from an independent promoter - Lluís Fajas; Jean‐Charles Fruchart; Johan Auwerx (1998)
PPARγ is a member of the peroxisome proliferator activated receptors (PPAR) subfamily of nuclear receptors. So far two PPARγ isoforms, PPARγ1 and PPARγ2, were known in mammals. We describe the structure of a novel human PPARγ subtype, PPARγ3. The PPARγ3 mRNA is transcribed from a novel promoter localized 5′ of exon A2. PPARγ3 mRNA expression was restricted to adipose tissue and large intestine. Similar to human PPARγ1 and ‐2, PPARγ3 is activated by thiazolidinediones and prostaglandin J derivatives and binds with high affinity to a PPRE.